Comparison of adenoid cystic carcinomas arising from the parotid gland vs. the submandibular gland: focus on systemic metastasis and tumor‐associated blood vessels. (23rd January 2014) - Shin, Da‐Yong; Jang, Kyu‐Sun; Kim, Bo Young; Choi, Ji Eun; Yoon, Heejei; Ko, Young‐Hyeh; Jeong, Han‐Sin
<x xml:space="preserve">Abstract</x> Background Although several studies reported that distant metastasis occurs more frequently in the tumors of submandibular gland (SMG) than parotid gland (PG), why SMG tumors preferentially metastasize to distant organs is not fully understood. We aimed to identify the differential tumor microenvironment for distant metastasis and possible underlying mechanisms. Methods We retrieved 27 cases of 1–4‐cm‐sized adenoid cystic carcinomas (ACCs) arising from the PG (n = 12) and SMG (n = 15). c‐KIT, VEGF‐R2, and CD31 staining were quantified by image‐based analysis to define the positive expression or tumor‐associated vessel areas in two representative sections per case. In addition, angiogenesis‐related genomic expression profiling was carried out to explore the underlying mechanism, which was confirmed by RT‐PCR and immunohistochemistry. Results Earlier systemic dissemination within 2 years was detected exclusively in SMG ACCs (5/15). The area of tumor‐associated blood vessels was larger in SMG ACCs than PG ACCs, and ACCs showing distant metastasis had greater blood vessel area than those without metastasis. Interestingly, normal SMG had more blood vessels per area than PG. Among angiogenesis‐related signals, the level of IL‐6 was significantly lower in SMG ACCs than PG ACCs. Moreover, IL‐6 expression decreased significantly in SMG ACCs compared with that in normal SMG, whereas it was up‐regulated in PG ACCs. Conclusion ACCs in the SMG microenvironment have more abundant tumor‐associated blood vessels than PG ACCs, which may explain the higher risk of distant metastasis from SMG tumors.